2019
DOI: 10.1039/c9ob00782b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the direct functionalization of quinoxalin-2(1H)-ones

Abstract: The direct C3-functionalization of quinoxalin-2(1H)-ones via C–H bond activation has recently attracted considerable attention, due to their diverse biological activities and chemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(75 citation statements)
references
References 141 publications
2
73
0
Order By: Relevance
“…The calculation of apparent quantum efficiency (450 nm) values for the two model reactions (Scheme b, see details in the Supporting Information, part VIII) further suggested that the generated radical did not undergo a chain propagation . Combining the results of the control experiments (Table ) and the above mechanistic investigations, on the basis of our previous work and other related reports, a plausible reaction pathway for this heterogeneous visible‐light‐accelerated C3 arylation and alkylation is proposed (Scheme c). At first, with the blue LED irradiation, the 2D‐COF‐1 is excited, and subsequently reduces the oxygen to generate the singlet oxygen radical and superoxide radical anion, which oxidizes the hydrazine 2 o with the loss of nitrogen and water, delivering the nucleophilic cyclohexyl radicals I .…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…The calculation of apparent quantum efficiency (450 nm) values for the two model reactions (Scheme b, see details in the Supporting Information, part VIII) further suggested that the generated radical did not undergo a chain propagation . Combining the results of the control experiments (Table ) and the above mechanistic investigations, on the basis of our previous work and other related reports, a plausible reaction pathway for this heterogeneous visible‐light‐accelerated C3 arylation and alkylation is proposed (Scheme c). At first, with the blue LED irradiation, the 2D‐COF‐1 is excited, and subsequently reduces the oxygen to generate the singlet oxygen radical and superoxide radical anion, which oxidizes the hydrazine 2 o with the loss of nitrogen and water, delivering the nucleophilic cyclohexyl radicals I .…”
Section: Methodssupporting
confidence: 53%
“…Among them, direct C3 arylation and alkylation have attracted more attention because the C3 arylated and alkylated quinoxalin‐2(1 H )‐ones always display unique properties and bioactivities as drug candidates . Consequently, a series of excellent methods for direct C3 arylation and alkylation of quinoxalin‐2(1 H )‐ones have been reported . Most of these are triggered by the addition of aryl or alkyl radical (Scheme ) which are mainly generated by direct radical initiation or catalytic single‐electron‐transfer (SET) process.…”
Section: Methodsmentioning
confidence: 99%
“…Other oxidants, such as PhI(OAc) 2 , K 2 S 2 O 8 and TBHP did not enhance the product yield ( Table 1, entries [2][3][4][5]. Subsequently, some organic solvents including dichloromethane (DCM), dichloroethane (DCE), toluene, tetrahydrofuran (THF), dimethyl formamide (DMF) and dimethylsulfoxide (DMSO) were explored (Table 1, entries 1,[6][7][8][9][10][11], and found that dichloromethane (DCM) was the optimal solvent for this transformation. After obtained the optimal oxidant and solvent, we tried to reduce the amounts of substrates 2 a and 3.…”
Section: Resultsmentioning
confidence: 99%
“…Quinoxalin‐2(1H)‐ones, well known as key scaffolds in many natural products, have attracted considerable attention since they display a diverse range of biological and pharmacological activities . Therefore, the functionalization of quinoxalin‐2(1H)‐ones has attracted considerable attention . In particular, more attention was paid to the synthesis of C3‐functionalized quinoxalin‐2(1H)‐one analogues, such as alkylation, arylation, acylation, amination, and phosphonation .…”
Section: Methodsmentioning
confidence: 99%
“…[8] Therefore, the functionalization of quinoxalin-2(1H)ones has attracted considerable attention. [9] In particular, more attention was paid to the synthesis of C3-functionalized quinoxalin-2(1H)-one analogues, such as alkylation, [10] arylation, [11] acylation, [12] amination, [13] and phosphonation. [14] Especially, the direct hydroxyalkylation, [10a] benzylation, [10b] oxyalkylation [10d] and cyanoalkylation [10c] of quinoxalin-2(1H)ones synthesis of 3-alkylquinoxalin-2(1H)-ones has been re-ported (Scheme 1, a-).…”
mentioning
confidence: 99%